Degradation of Aqueous Quinoline Using Persulfate Activated by γ‐Fe2O3@Carbon Composites and Enhanced by UV Irradiation. Issue 42 (9th November 2021) - Li, Xiaojuan; Ye, Ziyu; Liao, Fengzhen; Xie, Shuhan; Ye, Lanmei; Wang, Yongjing; Wang, Yonghao; Huang, Jian; Liu, Yifan
Abstract: In this study, the ultraviolet (UV) enhanced γ ‐Fe2 O3 @Carbon composite ( γ ‐Fe2 O3 @C) persulfate (PS) activation system was successfully constructed for quinoline degradation. Quinoline can be effectively degraded with the removal efficiency of 99 % and TOC removal efficiency of 86 % in 60 min at pH 7.5 due to the increased contribution of SO4 .− and . OH caused by the assistance of UV irradiation in the γ ‐Fe2 O3 @C/PS system. Control experiments showed that the quinoline removal efficiency might be primarily restricted by the limited PS dosage and the system had a wide pH application range of 3∼11, good tolerance and strong anti‐interference ability. In the presence of the reactive oxygen species (SO4 .−, . OH and 1 O2 ), quinoline was first decomposed into formic acid, aniline, ethylbenzene and other intermediate products through hydroxylation, oxidative dehydrogenation and ring‐opening reactions and then most of them were mineralized into carbon dioxide and water eventually. Abstract : An ultraviolet enhanced γ ‐Fe2 O3 @C composite persulfate activation system was successfully constructed for quinoline degradation. The auxiliary effect of ultraviolet can greatly improve the contribution ratio of free radicals (SO4 .− and . OH), which was beneficial to quinoline degradation and final mineralization.